Sharing innovative experiences. (New York United Nations Development Programme, 2010)
v.9. Examples of the successful conservation and sustainable use of dryland biodiversity.v.10. Examples of the development of pharmaceutical products from medicinal plants
UCASM-1725 (UCASM001725)
Keywords: Developing Countries; Economic development prospect; Sustainable development; Technological innovations